2010
DOI: 10.1128/jvi.02303-09
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosisPromotes HIVtrans-Infection and Suppresses Major Histocompatibility Complex Class II Antigen Processing by Dendritic Cells

Abstract: Mycobacterium tuberculosis is a leading killer of HIV-infected individuals worldwide, particularly in sub-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Paradoxically, recent reports suggest that M. tuberculosis contributes to HIV pathogenesis by promoting a shift in the dynamic balance between antigen processing and presentation of intact virion particles favoring trans-infection of HIV to T cells. These findings clearly emphasize that HIV and M. tuberculosis act synergistically with each infection contributing specific immune aberrations (62). Because of the critical role of CTLA-4 and TGF-␤ in establishment and propagation of these infectious diseases, these observations stress the urgency of development of novel therapeutic intervention strategies for CTLA-4-and TGF-␤-mediated impairment of the functional activity of DCs.…”
Section: Discussionmentioning
confidence: 69%
“…Paradoxically, recent reports suggest that M. tuberculosis contributes to HIV pathogenesis by promoting a shift in the dynamic balance between antigen processing and presentation of intact virion particles favoring trans-infection of HIV to T cells. These findings clearly emphasize that HIV and M. tuberculosis act synergistically with each infection contributing specific immune aberrations (62). Because of the critical role of CTLA-4 and TGF-␤ in establishment and propagation of these infectious diseases, these observations stress the urgency of development of novel therapeutic intervention strategies for CTLA-4-and TGF-␤-mediated impairment of the functional activity of DCs.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, mDC LPS have a greater ability to uptake and transmit viral particles than do iDC (4,6,8). In fact, it was recently shown that M. tuberculosis is able to mature DC, promoting similar phenotype of HIV-1 trans-infection and viral sequestration to those seen in LPS-stimulated DC, while suppressing class II Ag processing (19). Although both agonists would mature DC primarily by MyD88-dependent TLR-mediated mechanisms, little is known about the fate of captured particles in mDC LPS and whether they represent a source of viral Ags for HLA loading and T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well documented that the higher viral capture of mDC LPS results in increased trans-infection to target cells (4,6,8), little is known about the Ag-presentation ability of this DC subset. It was recently suggested that Mycobacterium tuberculosis promotes HIV-1 transinfection similarly to LPS, while suppressing class II Ag processing by DC (19). In this study, we address the efficiency of mDC LPS for presenting HIV-1-derived Ags to both CD4 + and CD8 + T cells.…”
mentioning
confidence: 99%
“…In brief, the donor cells (2 ϫ 10 5 ) were loaded with pseudotyped, single-cycle-infectious, luciferase-containing HIV-luc/JRFL or HIV-luc/HXB2 (10 ng p24 gag ) reporter virus, separately, for 2 h at 37°C, washed thoroughly, and then cocultured with Hut/CCR5 (2 ϫ 10 5 ) cells for 3 days or with phytohemagglutinin (PHA)-P-stimulated primary CD4 ϩ T cells (2 ϫ 10 5 ) for 5 days. Enhancement assays were performed as previously described (56,64); briefly, HIV-luc/JRFL (1 or 4 ng p24 gag ) (i) was loaded to basophils (2 ϫ 10 5 ) for 2 h and the pulsed basophils were cocultured with Hut/CCR5 cells for an additional 2 days or (ii) was added directly to Hut/CCR5 cells for 2 days of infection. A commercially available kit (Promega) was used to analyze viral infection by measuring luciferase activity in the cell lysate.…”
Section: Methodsmentioning
confidence: 99%